Phylogeography and population genomics of the critically endangered aquatic plant Caldesia grandis in China - Yan, Dong-Ying; Peng, Shuai; Lehtonen, Samuli; Chen, Jin-Ming; Li, Zhi-Zhong (Elsevier BV, 2025)
Caldesia grandis, a critically endangered aquatic species, is predominantly found in the mid-low mountainous swamps of subtropical China. This study assessed the genetic diversity and population structure of the species using RAD-seq data, explored its phylogeography across the extant nine populations based on five plastid DNA (ptDNA) regions, and conducted niche modeling analysis. We found low genetic diversity (HE = 0.180, Ho = 0.222, and π = 0.197) and genetic differentiation among populations (Fst = 0.089), which was likely due to genetic drift in small populations and frequent inter-population contact during the Quaternary period. Although RAD-seq analysis did not reveal a clear population structure, two distinct clades, comprising western and eastern populations, were identified using five ptDNA haplotypes. Molecular dating and niche modeling suggested that the uplift of the Luoxiao Mts may have contributed to the divergence of the eastern and western clades (ca. 1.51 Ma)during the Pleistocene, which also supports the hypothesis that the Nanling Mts acted as a refugium for C. grandis. Additionally, the repeated glacial periods of the Quaternary, accompanied by contraction and expansion of suitable habitats, likely facilitated gene exchange among populations, influencing the current distribution pattern in subtropical China. Our results suggested that each ptDNA haplotype should be treated as an independent unit for conservation purposes, and ex-situ efforts should be prioritized to conserve C. grandis in China.